"Network Security: Private Communication in a PUBLIC World, Now Includes Ispec, SSL, PKI, AES, and Web Security" - Kaufman (Charlie); Perlman (Radia); Speciner ( Mike) (2006)
Network Security
22.5
Keywords: Network Security